What Girls Want: An Affective Reading of Using Pair Interviewing Methods to Research Activist Girls and Their Relationships with Their Mothers and Mother Figures - Maitland, Hannah (Atlantis, 2024)
This paper is a critical reflection on the fieldwork and analysis stage of my dissertation project on activist girls. My project explores how an intergenerational lens can be critically applied to the actions and motivations of activist girls and asks how contemporary girls negotiate and feel about their activism, their relationships with their mothers and communities, and their imaginings for a feminist future. Between 2021 and 2022, I conducted semi-structured in-depth interviews with ten activist girls (aged 11-20) and their mothers/mother figures in a series of one-on-one and paired interviews. In this paper, I reflect on the affective landscape that emerged when interviewing girls, not only about their mothers but also with their mothers, and what this methodology might offer to the field of girls’ studies. I engage with how daughters and mothers negotiate, express, and sometimes struggle to articulate their desires for the future and their relationship in the context of the paired interviews and how both the subject matter and method of this study posed challenges for me as a researcher.